Inferring Query Intent from Reformulations and Clicks - Radlinski, Filip; Szummer, Martin; Craswell, Nick (Proc. 19th Annual International World Wide Web Conference (WWW '10)., 2010)
Many researchers have noted that web search queries are often ambiguous or unclear. We present an approach for identifying the popular meanings of queries using web search logs and user click behavior. We show our approach to produce more complete and user-centric intents than expert judges by evaluating on TREC queries. This approach was also used by the TREC 2009 Web Track judges to obtain more representative topic descriptions from real queries.